2014
DOI: 10.1080/02614367.2014.986507
|View full text |Cite
|
Sign up to set email alerts
|

For the benefit of all? Developing a critical perspective in mega-event leverage

Abstract: The purpose of this article is to bring to light the need for developing a critical leveraging perspective on mega-events and propose a research agenda that extends the focus of the leverage concept towards this direction. Current research on leverage focuses on the attainment and magnification of mega-event outcomes. A critical lens of inquiry however is needed to move forward and take into account the influence of power structures and social ordering processes on developing and implementing strategic leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 60 publications
(57 reference statements)
0
36
0
1
Order By: Relevance
“…This ideological rationale frames event policy objectives to primarily align with destination branding and economic impact, while incentivizing private sector involvement. The principal risks associated with a highly entrepreneurial event governance include inequality, marginalization, and social polarization (Foley, McGillivray, & McPherson, 2011) as elite groups with more access to resources and capital may benefit at the expense of weaker social groups (Ziakas, 2015). To tackle this problem, stakeholder inclusiveness and participation in event planning and governance is vital to facilitate equal distribution of impacts and benefits.…”
Section: Planning and Governance Shaping Event Portfoliosmentioning
confidence: 99%
“…This ideological rationale frames event policy objectives to primarily align with destination branding and economic impact, while incentivizing private sector involvement. The principal risks associated with a highly entrepreneurial event governance include inequality, marginalization, and social polarization (Foley, McGillivray, & McPherson, 2011) as elite groups with more access to resources and capital may benefit at the expense of weaker social groups (Ziakas, 2015). To tackle this problem, stakeholder inclusiveness and participation in event planning and governance is vital to facilitate equal distribution of impacts and benefits.…”
Section: Planning and Governance Shaping Event Portfoliosmentioning
confidence: 99%
“…For instance, Misener and Mason (2006) found that people who actively participate in sportive or cultural expression can be empowered through opportunities to be creative, develop and use skills, and contribute to inclusive social and cultural identities. These findings provide the precondition for the third and most recent similarity observed in event impact studies, namely the increased importance placed on a strategic and sustainable approach to planning and managing the diverse impacts generated (Nichols & Ralston, 2015;Reis & Sperandei, 2014;Ziakas, 2014).…”
Section: Events Social Impact and Leveragingmentioning
confidence: 99%
“…Leveraging refers to the idea that the positive impacts from events are not simply an automatic result of hosting events; rather, it depends on SOCIAL VALUE OF SPORT EVENTS 7 how the event and related resources are utilized to create the desired outcomes (see Chalip, 2006;Chalip & O'Brien, 2008). Thus, unlike the catch-all concept of legacy as defined by Preuss (2007) to be everything left (positive, negative, planned, and unplanned) after an event-which has no strategic imperative-leveraging emphasizes the importance of planning before, during, and after the event to create positive impacts and lasting outcomes (see, for example, Pereira, Mascarenhas, & Pires, 2014;Smith, 2010;Ziakas, 2014). In the sport for development literature, leveraging events has become a prominent means of understanding how to strategically utilize the event to create target outcomes for local communities (Schulenkorf, 2012).…”
Section: Events Social Impact and Leveragingmentioning
confidence: 99%
“…Secondly, with smaller scale events there is "the potential for tighter social networks and connectedness of the local population with the event, be it as politicians, spectators, volunteers, marketing destination managers, or event organizers" (Misener, Taks, Chalip, & Green, 2015, p. 4). By utilizing local infrastructure and building on community resources, small-scale or community events are more likely to maximize the direct benefits for their host communities than a mega-event might (Smith, 2012;Ziakas, 2015).…”
Section: Sport Events In Low-and Middle-income Countries 219mentioning
confidence: 99%